Opportunities and Challenges of e-Learning-based Learning: A Case in Indonesian Learning - Suryaman, Maman (Ikaprobsi, 2023)
In the world of education, the direct impact of the Covid-19 pandemic is the closure of schools and the learning process is carried out online. School closures are carried out to reduce the mass spread of the virus and save the world of education from the loss of quality generations in the future. However, at the same time the development of information and communication technology (ICT) which is very fast and can be a problem solver becomes a solution that learning is guaranteed to take place through electronic learning models. On the other hand, there is anxiety among teachers, students, and parents. They must master ICT devices in the shortest possible time. These opportunities and challenges come together so that adaptability of all parties is needed. The question is how the opportunities and challenges of learning through electronic learning in Indonesia and how the implementation of Indonesian learning during the pandemic is associated with electronic learning. First, the challenges faced by teachers are the willingness to be technologically literate, online teaching materials, internet networks, the availability of laptops, devices, software, human resources of educators and technicians, ICT infrastructure, training support, electrical power support, ICT utilization policy support for learning, and limited sarpras in certain areas; The opportunities are ease of communication between teachers and students, structured and scheduled teaching materials, easy access to teaching materials and discussions in large quantities. Second, electronic learning in the case of Indonesian learning illustrates that there are still many problems to be resolved related to the implementation of electronic learning.